Investigation of three-body force effects in neutron-deuteron scattering at 95 MeV - P. Mermod (2018)
We have measured the neutron-deuteron (nd) elastic-scattering differential cross section at 95 MeV incident neutron energy, using both the Medley and the SCANDAL setups at TSL in Uppsala. The full angular distribution was covered by detecting recoil deuterons from thin CD2targets, and the result was normalized to the neutron-proton (np) cross section. Recent theories predict that three-nucleon (3N) force effects, if present, would affect the cross section in the minimum region by about 30%. The results are compared with theoretical calculations and are well described if 3N forces are included. © 2005 American Institute of Physics.